Non-fullerene acceptors with alkylthiothiophene side chains for efficient non-halogenated solvent processed indoor organic photovoltaics. Issue 42 (24th October 2022) - An, Na Gyeong; Lee, Ji Eun; Lee, Woojin; Yuk, Dohun; Song, Seyeong; Wang, Chanjie; Kwon, Soon-Ki; Kim, Yun-Hi; Kim, Jin Young
Abstract : New non-fullerene acceptors were synthesized by alkylthiothiophene side chain engineering and the material systems based on the acceptors demonstrated non-halogenated solvent processed indoor organic photovoltaics with an efficiency of 22.38% under 500 lux LED light. Abstract : Organic photovoltaics (OPVs) are regarded as promising energy sources for powering internet of things devices under indoor conditions. Indoor OPVs (IOPVs) have achieved power conversion efficiencies (PCEs) of 25–30%, due in part to the discovery of wide band gap non-fullerene acceptors (NFAs) (>1.7 eV). However, this requires the use of halogenated solvents that are harmful to human health and the environment. Therefore, halogen free solvent processing with the deliberate designing wide band gap NFAs is required to demonstrate the feasibility and environmental compatibility of NFA-based IOPVs. Herein, we designed two NFAs, ITIC-Th-s and ITIC-Th-s-me, composed of an ITIC core and four 5-thioalkylated-2-thienyl groups as out-of-side chains with methyl groups attached to the conjugated end units. The substitution of electron-donating methyl in the end group is expected to increase an open-circuit voltage, which is beneficial to IOPV applications. They were then blended with a polymer donor (PM6) to obtain a photoactive layer with an absorption spectrum similar to that of indoor light sources. Xylene:1, 8-octanedithiol (XO) and chlorobenzene:1, 8-diiodooctane (CD) were used as non-halogenated and halogenated solvents, respectively. XO-based devices exhibited competitive PCEs relative to CDs; PM6:ITIC-Th-s and PM6:ITIC-Th-s-me yielded PCEs of ∼19% and ∼22%, respectively, under common white light emitting diode illumination. Specifically, PM6:ITIC-Th-s-me processed from XO solvents achieved a PCE of 22.38% at 550 lux, which is the best-performing binary material system based IOPVs processed from a non-halogen solvent mixture. The presented approach highlights several useful design strategies for the development of indoor NFAs for efficient non-halogenated IOPV applications.